Perhitungan Beban Pendingin Dan Kinerja Kotak Refrigerasi Ikan Kapasitas 35 L - Generousdi (Riset Sinergi Indonesia, 2022)
The coolant load test in the cooler with a capacity of 35 L uses 1 kg of lambak fish. The purpose of this research is to determine the load on the fish cooler to determine whether the heat load is sufficient for the refrigeration process. This fish cooling method uses vapor compression, therefore a fish cooler box is made that is effective and has innovations that can cool food ingredients so they last a long time. The results of the fish cooler box power test were 0.077 kW at compressor power, flow rate 0.00247 kg/s, evaporator heat 0.2758 kW, actual COP 3.581, COP carnot 4.478, and efficiency 79.97%. Fish that is put in the cooler for 2 hours will drop in temperature to -11℃. The performance of this compressor is very good and ideal with a maximum load of 15 kg.